Analisis Hubungan Inisiasi Menyusu Dini (IMD) Terhadap Pemberian Asi Eksklusif Di Wilayah Kerja Puskesmas Makrayu Kota Palembang - Nina Deslima (Sinergi : Jurnal Ilmiah Multidisiplin, 2026)
Background: Exclusive breastfeeding coverage at Makrayu Community Health Center remains low at 63.6% despite significant improvement in early initiation of breastfeeding implementation reaching 97.3%. This disparity indicates other factors influencing exclusive breastfeeding success beyond early initiation of breastfeeding practice. Objective: To analyze the relationship between early initiation of breastfeeding and exclusive breastfeeding practice in the working area of Makrayu Community Health Center, Palembang City. Methods: Descriptive analytical study with cross-sectional design involving 110 respondents selected through purposive sampling. Data were collected through interviews using validated questionnaires and analyzed using chi-square test and multiple logistic regression with significance level α=0.05. Results: There was a significant relationship between early initiation of breastfeeding and exclusive breastfeeding (p=0.001; PR=1.616). Multivariate analysis showed health worker support as the dominant factor (OR=9.249; p=0.005) followed by early initiation of breastfeeding (OR=4.052; p=0.045). Other significantly related variables were education, knowledge, attitude, formula promotion attraction, and family support. Conclusion: Health worker support and early initiation of breastfeeding implementation are primary determinants of exclusive breastfeeding success. Keywords: Early Initiation of Breastfeeding, Exclusive Breastfeeding, Health Worker Support Abstrak Latar Belakang: Cakupan ASI eksklusif di Puskesmas Makrayu masih rendah sebesar 63,6% meskipun pelaksanaan inisiasi menyusu dini mengalami peningkatan signifikan mencapai 97,3%. Disparitas ini mengindikasikan adanya faktor-faktor lain yang mempengaruhi keberhasilan pemberian ASI eksklusif selain pelaksanaan inisiasi menyusu dini. Tujuan: Menganalisis hubungan inisiasi menyusu dini terhadap pemberian ASI eksklusif di wilayah kerja Puskesmas Makrayu Kota Palembang. Metode: Penelitian deskriptif analitik dengan desain cross sectional melibatkan 110 responden yang dipilih secara purposive sampling. Data dikumpulkan melalui wawancara menggunakan kuesioner tervalidasi dan dianalisis dengan uji chi square serta regresi logistik berganda menggunakan tingkat kemaknaan α=0,05. Hasil: Terdapat hubungan bermakna antara inisiasi menyusu dini dengan pemberian ASI eksklusif (p=0,001; PR=1,616). Analisis multivariat menunjukkan dukungan petugas kesehatan sebagai faktor dominan (OR=9,249; p=0,005) diikuti inisiasi menyusu dini (OR=4,052; p=0,045). Variabel lain yang berhubungan bermakna adalah pendidikan, pengetahuan, sikap, ketertarikan promosi susu formula, dan dukungan keluarga. Kesimpulan: Dukungan petugas kesehatan dan pelaksanaan inisiasi menyusu dini merupakan determinan utama keberhasilan pemberian ASI eksklusif. Kata Kunci: Inisiasi Menyusu Dini, ASI Eksklusif, Dukungan Petugas Kesehatan